Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan: Studi Pada Warung Bakso Bacit Pelanggan Perempuan di Parungponteng Tasikmalaya - Seli Yulianti; Dadang Munandar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the influence of service quality and price on female customer satisfaction at Warung Bakso Bacit Parungponteng, Tasikmalaya. The research was motivated by a decline in customer numbers, complaints about service quality, and perceptions of inadequate pricing, which are suspected to influence customer satisfaction. The study used a quantitative method with a descriptive and verification approach. The sample consisted of 94 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS. The results showed that service quality and price each had a positive and significant effect on customer satisfaction, and simultaneously had a positive and significant effect on customer satisfaction. These findings suggest that improving service quality and setting appropriate prices can increase female customer satisfaction at Warung Bakso Bacit Parungponteng.